Kompresi File Video Menggunakan Algoritma Yamamoto’s Recursive Code - Butar-Butar, Ronaldo P. (Bulletin of Data Science, 2023)
At this time it is very common to use it in all aspects, from advertising, films, even learning during the COVID-19 pandemic using video media as a learning medium. Large video file sizes can reduce free space on storage media such as hard drives, flash drives and so on. The more videos that are stored, the less free space is left, or even no free space is left on the storage media. This will not cause a problem if the storage media used has a large capacity, but not everyone has a large storage media. One way to overcome this problem is to use compression techniques. Data compression is a process of converting a set of data into a form of code to save the need for data storage. On this basis, the application of Yamamoto's Recursive Code Algorithm in Compressing Video Files is made in order to help users compress video files that are initially large into their smallest size. Video compression is the opposite of digital video data compression. Compression is the conversion of data to a smaller format, usually done so that data can be stored or transmitted more efficiently. The process of recovering data that has been reduced is called decompression.